Peran Majlis Dzikir Al Khidmah Dalam Mengurangi Kenakalan Remaja Di Dusun Bali Desa Plumpang Kecamatan Sukodadi Kabupaten Lamongan - Syaiful Ulum, Fadhillah; Habibah, Sulhatul; Sun'iyah, Siti Lathifatus (Jurnal Murid, 2025)
This research aims to describe the types of juvenile delinquency in Bali Hamlet, Plumpang Village, SukodadiDistrict, Lamongan Regency. The background of this research is that delinquency is often committed by teenagers nowadays, therefore this delinquency must be addressed immediately. One effort to overcome this is by holding Al Khidmah dhikrassembly activities. Majlis Dhikr Al-Khidmah is anorganization, which was founded directly by Hadratussyaikh H. Ahmad Asrori Al Ishaqi Ra. on December 25 2005 at the As Salafi Al-Fitrah Meteseh Islamic Boarding School,Semarang, Central Java. Majlis dhikr Al-Khidmah inremembrance of Allah SWT is carried out together, by reading istighosah, manaqib of Sheikh Abdul Qodir and MaulidurrasulSaw. As well as praying for parents, ancestors, teachers andMuslim spirits wal muslimat al akhyai minhum wal amwat. The aims of this research are: (1) To determine juveniledelinquency in Bali Hamlet, Plumpang Village, SukodadiDistrict, Lamongan Regency. (2) To determine the role of the Al Khidmah dhikr assembly in reducing juvenile delinquency in Bali Hamlet, Plumpang Village, Sukodadi District, Lamongan Regency. This research uses qualitative methods,where the data collection process uses interview, observation and documentation methods. The results of this research are: (1) The condition of Balinese Hamlet teenagers before participating in the Al-Khidmah dhikr assembly was difficult to accept advice and was easily influenced by negative things. Meanwhile, after attending the Al-Khidmah dhikr assembly, teenagers are more respectful of their parents, behave better and feel calm. (2) Majlis dhikr Al-Khidmah plays a role inreducing juvenile delinquency and also as a controller of teenagers so that they remain in a state of faith and can avoid negative influences. These efforts have provided benefits and good impacts on teenagers, namely change the mindset ofteenagers, teenagers can use their time for useful things, teenagers understand more about religion and teenagers can control themselves not to commit juvenile delinquency and behave better than before.